An Investigation into Strategic Alliances and Their Effects on Brand Awareness: A Quantitative Study of the United States' Professional Sports Industry - Smith, Staceylyn (2016)
The following study aims to answer the research question: In the United States professional sports industry, does the implementation of a strategic sports alliance affect the brand awareness of the teams involved? This was done by conducting exploratory research in two United States cities, one with a strategic sports alliance in place and one without. Quantitative methods were used to survey participants from both of these locations to measure their brand awareness levels for the professional sports teams that are located in their particular city. After the collection of responses was complete, the data was then analysed by several different means to determine if a relationship existed between the existence of a strategic alliance and the brand awareness of each of the teams involved. The results from this study provide an initial starting block for future research to build upon in further exploration of the formation of strategic alliances in the United States’ professional sports industry.